Genetic insights into alcohol-associated liver disease: integrative transcriptome-wide analysis identifies novel susceptibility genes - Wang, Qianchang; Wang, Zhe; Hu, Minzhe; Liu, Fangfeng; Wang, Zhengjian (Frontiers in Medicine, 2025)
BackgroundAlcohol-associated liver disease (ALD) is a chronic condition influenced by both genetic and environmental factors. While GWAS has identified ALD-related loci (PNPLA3, MBOAT7, TM6SF2), underlying genetic mechanisms and therapeutic targets remain unclear.MethodsThis study utilized the FinnGen R12 dataset (488,982 participants) and GTEx v8 eQTL data to perform a cross-tissue transcriptome-wide association study (TWAS) using UTMOST, with single-tissue validation via FUSION. Gene-level association analysis (MAGMA), Mendelian randomization (MR), and colocalization were applied to evaluate causal links. Functional significance was assessed through GeneMANIA, drug enrichment, and molecular docking analyses.ResultsThree ALD susceptibility genes—AFF1, C4orf36, and HSD17B13—were identified and validated. HSD17B13 may reduce ALD risk via lipid metabolism and redox balance, while AFF1 is implicated in transcription regulation. C4orf36 requires further study. Drug enrichment analysis highlighted AFF1 as a target for beta-D-allopyranose, dexbrompheniramine, and (+)-chelidonine, with molecular docking confirming strong binding potential.ConclusionThis study identifies AFF1, C4orf36, and HSD17B13 as ALD susceptibility genes, proposing AFF1 as a potential therapeutic target, paving the way for precision medicine in ALD, though further experimental validation is needed to establish their functional relevance.